The genetic landscape of inherited retinal dystrophies in Arabs - Lama Jaffal; Hawraa Joumaa; Jinane Noureldine; Malak Banjak; Mariam Ibrahim; Zamzam Mrad; Ali Salami; Said El Shamieh (BMC, 2023)
Abstract Inherited retinal dystrophies (IRDs) are a major cause of vision loss. Altogether are highly heterogeneous genotypically and phenotypically, exhibiting substantial differences worldwide. To shed more light on these conditions, we investigated the genetic and phenotypic landscape of IRDs in the Arabs globally and per country. We analyzed 1,621 affected individuals from 16 Arabic countries reported in 198 articles. At the phenotypic level, rod-cone dystrophy (RCD) and Usher syndrome were the most prevalent conditions among non-syndromic and syndromic IRDs. At the gene level, TULP1, ABCA4, RP1, CRB1, MYO7A, RPE65, KCNV2, and IMPG2 were the most mutated genes. Interestingly, all except CRB1 were highly prevalent because they harbored founder mutations, implying that consanguinity is a major determinant in Arab countries. Of note, ~ 93% of the investigated individuals carried homozygous mutations. The country analysis for the IRDs conditions and their associated genotypes revealed that whereas Leber Congenital Amaurosis, RCD, and USHER syndrome were widely distributed, bestrophinopathies and non-syndromic hearing loss were restricted to specific countries (till now). This study could be a starting point for initiating suitable health policies towards IRDs in the Arab world. The high degree of homozygosity urges the need for genetic counsellors to provide personalized information and support the affected individuals.